Analisis Kesulitan Belajar Matematika pada Materi Penjumlahan dan Pengurangan di MIs Yayasan Azis Al Akbar - Dalila, Sastri; Balqis, Ratika; Wandini, Rora Rizki (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Many students at Azis Al Akbar Elementary School are having trouble understanding addition and subtraction in basic arithmetic. This research aims to identify the difficulties in learning mathematics among lower-grade students. The researcher used a qualitative descriptive approach. The study subjects were 13 students, including 2 boys and 10 girls. Data was collected through interviews, tests, and document studies. The results showed that: 1) students' reading abilities are still lacking, making it difficult for them to understand, 2) difficulties in counting more than two digits are still low, 3) difficulties in understanding addition and subtraction operations, and 4) students' lack of interest in learning due to minimal parental encouragement. Based on these findings, the researcher hopes that teachers can teach and introduce addition and subtraction operations to students so that they can understand them.